The Path to Eliminating Cervical Cancer in Canada: Past, Present and Future Directions - Hannah Caird; Jonathan Simkin; Laurie Smith; Dirk Van Niekerk; Gina Ogilvie (Current Oncology, 2022)
Cervical cancer remains a common cancer affecting women in Canada. While cervical cancer incidence and mortality in Canada have declined for several decades due to the success of organized, provincial cervical cancer screening programs, further decreases will require enhancement of primary, secondary, and tertiary prevention efforts. The present commentary provides a historical overview of cervical cancer trends in Canada, presents current statistics on cervical cancer incidence, mortality and survival, and discusses future directions in relation to cervical cancer elimination.